Large Magnetoelectric Coupling in a Y‐Type Hexaferrite. Issue 3 (15th August 2019) - Yang, Yanting; Jiang, Kaidi; Wu, Qiong; Ge, Hongliang
Abstract : The enhanced magnetoelectric properties of Ba0.5 Sr1.5 Zn2 (In0.08 Fe0.92 )12 O22 are demonstrated. This hexaferrite exhibits great magnetoelectric tunability and high electrical resistivity. Mutual modulation of ferroelectricity and magnetism is simultaneously achieved near room temperature. Moreover, the reversal of M direction by an electrical field is obtained at low magnetic field. This study illuminates a potential application in magnetoelectric devices. Abstract : The cross‐coupling between electric polarization and magnetization in multiferroic materials provides a great potential for low‐energy‐consuming storage devices. Great magnetoelectric tunability and high electrical resistivity are obtained in Ba0.5 Sr1.5 Zn2 (In0.08 Fe0.92 )12 O22 . Mutual modulation of ferroelectricity and magnetism is simultaneously achieved near room temperature. Electrical control of magnetization direction reversal is also obtained. The studies illuminate a potential application in magnetoelectric devices.